THE SIGNIFICANCE OF THE REQUEST FOR EXTRAORDINARY REVIEW OF VALIDITY OF THE FINAL VERDICT IN THE PROTECTION OF SUBJECTIVE RIGHTS OF THE PARTIES IN ADMINISTRATIVE DISPUTE (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
Since 2010 extraordinary legal remedy has been used in the Croatian system of administrative adjudication known as the request for extraordinary review of legality of the final verdicts. Through the grammatical, logical and teleological methods of interpretation, the paper analyzes the provisions of the Administrative Disputes Act from 2010 regulating this remedy. Changes of the norms of the remedy made in accordance with the amendments of the Administrative Dispute Act from 2012 and 2014 are briefly mentioned. The specificities of submitting legal remedy are especially emphasized in terms of its reasons, applicants, deadlines and contents of the request, grounds for review and the authorities of the Supreme Court of the Republic of Croatia in deciding on the submitted applications. Furthermore, there are indications of certain imprecision and lack of legal regulation. Statistical data of the State Attorney Office of the Republic of Croatia and the court practice of the Supreme Court of the Republic of Croatia in the period from 2012 to 2017 in reference with the submitted requests which are analyzed based on casuistic methods. A special chapter is devoted to a brief review of the normative regulation of legal remedy in Serbia, Bosnia and Herzegovina and Montenegro, using a comparative method and in conclusion final considerations of the scientific issues are presented.